Effects of baseline abdominal pain and bloating on response to lubiprostone in patients with irritable bowel syndrome with constipation. Issue 10 (27th September 2016) - Chang, L.; Chey, W. D.; Drossman, D.; Losch‐Beridon, T.; Wang, M.; Lichtlen, P.; Mareya, S.
Summary: Background: Lubiprostone (8 μg b.d.) received US Food and Drug Administration (FDA) approval in 2008 for the treatment of constipation‐predominant irritable bowel syndrome (IBS‐C) in women aged ≥18 years. In 2012, the FDA issued new guidance for IBS‐C clinical trials, recommending a composite endpoint incorporating both abdominal pain and stool frequency. Aim: In a post hoc analysis, similar criteria were applied to data from two pivotal, phase 3, double‐blind, randomised trials of lubiprostone in patients with IBS‐C. Methods: Included patients had a baseline spontaneous bowel movement (SBM) frequency <3/week and abdominal pain or bloating ratings ≥1.36 on a 5‐point scale [0 (absent) to 4 (very severe)]. Responders (composite endpoint) had a mean pain reduction ≥30% compared with baseline, and an increase from baseline of ≥1 SBM/week for ≥6 of the 12 treatment weeks. Lubiprostone effects on abdominal pain alone were also evaluated, as were bloating alone and in a composite endpoint with stool frequency. Results: In pooled data, 325 patients received lubiprostone and 180 received placebo. Rates of response were higher with lubiprostone vs. placebo for the composite endpoint of improved pain and stool frequency (26.3% vs. 15.3%, respectively; P = 0.008) and the composite endpoint of improved bloating and stool frequency (23.8% vs. 12.6%, respectively; P = 0.012). Response rates were also higher with lubiprostone vs. placebo for abdominal pain alone ( P = 0.005) and bloating alone ( P = 0.012). Conclusion: Lubiprostone was significantly more effective than placebo in improving abdominal pain or bloating, and also in composite endpoints that included stool frequency.